5HT3 Antagonists versus Dexamethasone in the Prevention of PONV in Patients Undergoing Laparoscopic Cholecystectomy: A Meta-Analysis of RCTs. (6th November 2016) - Zhou, Chengmao; Zhu, Yu; Liu, Zhen; Ruan, Lin
Abstract : Background . 5HT3 antagonist, an antiemetic alternative to dexamethasone, is an effective drug for the prevention of postoperative nausea and vomiting (PONV). Methods . PubMed and The Cochrane Library (from inception to June 2016) were searched for relevant RCTs (randomized controlled trials). Results . Seven trials, totaling 682 patients, were included in this meta-analysis. This meta-analysis demonstrated that 5HT3 antagonist was as effective as dexamethasone in preventing PONV (RR, 1.12; 95% CI, [0.86, 1.45]; P = 0.40 ) within 24 hours of laparoscopic cholecystectomy, and no significant heterogeneity was observed among the studies (I 2 = 0 % ; P = 0.98 ). During the early postoperative period (0–6 h), 5HT3 antagonists were superior to dexamethasone in reducing POV (RR, 0.31; 95% CI, [0.11, 0.93]; P = 0.04 ), while, in other postoperative stages (6–12 h, 12–24 h, and 0–24 h), it was not more effective in the prevention of POV than dexamethasone. And no significant difference was found in the prevention of PON between 5HT3 antagonists and dexamethasone at different postoperative periods (0–6 h, 6–12 h, 12–24 h, and 0–24 h). Conclusions. As a result, it is advisable to encourage 5HT3 antagonists as an alternative to dexamethasone for the prevention of PONV in patients undergoing laparoscopic cholecystectomy.